The Role of Men in Breast Cancer Campaigns: An In-Depth Study on How Husbands and Brothers Serve as Key Advocates for Early Screening in Patriarchal Regions - Irma Irma; Nurlina Subair (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aims to examine the participation of husbands/male siblings as promotional agents for early breast cancer screening in patriarchal regions and to analyze the dynamics of their involvement in women's health campaigns. This research employs a qualitative approach with a case study method conducted in Mamuju Regency during January-February 2025. The research subjects consisted of 24 respondents (12 males and 12 females) selected through purposive sampling. Data collection was carried out through in-depth interviews, focus group discussions (FGD), participatory observation, and questionnaires. Qualitative data analysis utilized thematic analysis with triangulation, while quantitative data were analyzed descriptively. The findings reveal a significant paradox between high participation motivation and low knowledge levels among males. The average knowledge of males regarding breast cancer was only 34.6% compared to 66.9% for females, with the largest gap in aspects of breast self-examination (BSE) methods (17% vs 58%) and risk factors (33% vs 75%). Nevertheless, male participation motivation was remarkably strong, driven by personal factors (loss experiences), relational factors (family affection), and religious factors (religious obligations). Male involvement was proven to increase female compliance with early detection by 75% and create a dynamic support system within households. Male participation as promotional agents for early breast cancer screening in patriarchal regions proves effective despite knowledge limitations. Caring masculinity can develop within patriarchal contexts through strategic reframing without eliminating traditional masculine identity. Effective intervention strategies include religious legitimization, familial approaches, and empowerment of accompanying roles. This research demonstrates that emotional engagement and procedural support can compensate for cognitive limitations in health advocacy, providing new insights for developing gender-sensitive health promotion programs in patriarchal societies.